2005
DOI: 10.1007/s10935-005-1832-4
|View full text |Cite
|
Sign up to set email alerts
|

Characteristics of Natural Mentoring Relationships and Adolescent Adjustment: Evidence from a National Study

Abstract: This research investigated characteristics of natural mentoring relationships (mentor role, frequency of contact, closeness, duration) as predictors of adjustment outcomes among older adolescents and young adults (N = 2,053) in the Add Health study. Outcomes were assessed in the domains of education/work, problem behavior, psychological well-being, and physical health. Mentoring relationships with persons in roles outside of the family predicted greater likelihood of favorable outcomes in all domains except ps… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

17
164
1
2

Year Published

2006
2006
2018
2018

Publication Types

Select...
3
2
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 180 publications
(184 citation statements)
references
References 29 publications
17
164
1
2
Order By: Relevance
“…The study also examined the correlates of individual mentoring features, an area that needs to be better understood to inform the design of mentoring programs. 34 In this study, 62% of the sample reported the presence of an unrelated natural mentor. Sixtytwo is a high percentage rate when compared to similar studies among youths in the general population.…”
Section: Discussionmentioning
confidence: 57%
See 1 more Smart Citation
“…The study also examined the correlates of individual mentoring features, an area that needs to be better understood to inform the design of mentoring programs. 34 In this study, 62% of the sample reported the presence of an unrelated natural mentor. Sixtytwo is a high percentage rate when compared to similar studies among youths in the general population.…”
Section: Discussionmentioning
confidence: 57%
“…33 In addition, a study utilizing a nationally representative sample of adolescents reported that 72.9% of the sample identified a natural mentor. 34 More recently, studies have begun to examine the nature (i.e., structure and quality) of supportive relationships. Some studies focus on the structural features of the relationship, such as duration and frequency of contact.…”
Section: Introductionmentioning
confidence: 99%
“…Their results show, overall, a significant positive effect of mentoring on the odds of employment (DuBois and Silverthorn, 2005b), although among those who report having a mentor, specific characteristics of the mentoring relationships were not associated with employment (DuBois and Silverthorn, 2005a). In their study, employment was examined alongside 17 other dependent variables related to educational attainment, problem behavior, psychological wellbeing, and physical health.…”
Section: Mentors In Young Livesmentioning
confidence: 99%
“…The only exception comes from the research of DuBois & Silverthorn (2005a;2005b), who used data from Add Health to explore the effects of informal mentoring on employment. Their results show, overall, a significant positive effect of mentoring on the odds of employment (DuBois and Silverthorn, 2005b), although among those who report having a mentor, specific characteristics of the mentoring relationships were not associated with employment (DuBois and Silverthorn, 2005a).…”
Section: Mentors In Young Livesmentioning
confidence: 99%
“…[17] Disparities become further magnified in ethnic minorities. [4][5][6][7][8]13,18] Beyond healthcare access, disease knowledge, and TR, studies show a mentoring relationship (MR) [19][20][21] for adolescents with chronic disease is crucial for successful transition to adult care. [22] The transition period is a vulnerable time for adolescents with CHD, and many drop out of active health care.…”
Section: Introductionmentioning
confidence: 99%